The Comparison of Total Phenolics, Total Antioxidant, and Anti-Tyrosinase Activities of Korean Sargassum Species - Su Hyeon Baek; Lei Cao; Seung Jin Jeong; Hyeung-Rak Kim; Taek Jeung Nam; Sang Gil Lee (Journal of Food Quality)
Sargassum species, a group of marine brown algae consumed in Asian countries, have shown various health benefits, such as improving the conditions of cardiovascular disease, osteoarthritis, and hypopigmentation. Also, these benefits are associated with their phenolic content and strong antioxidant capacities. However, the antioxidant capacities of different Sargassum species had not been thoroughly explored and compared. Thus, this study aimed to compare the total phenolic contents, total flavonoid contents, total antioxidant capacities, and anti-tyrosine activity of eleven Sargassum species harvested off the Korean coast. The results revealed that the total phenolic content (from 20.57 to 88.97 mg gallic acid equivalent/g dry weight (dw)), flavonoid content (from 22.08 to 82.33 mg quercetin equivalent/g dw), anti-tyrosinase activity (from 13.30 to 126.30 mg kojic acid equivalent/dw), and antioxidant capacities of the 11 Sargassum species had wide ranges. Among them, S. miyabei Yendo and S. hemiphyllum showed the highest total antioxidant capacities while S. miyabei Yendo exhibiting the highest total phenolic and flavonoid contents. The highest anti-tyrosinase activity was seen in S. fillicinum and S. yendoi. Sargahydroqunoic acid and sargachromanol, two alga-derived meroterpenoid compounds with strong antioxidant activity, were detected and quantified in S. miyabei Yendo and S. serratifolium. Our findings guarantee further investigation of the health benefits of Sargassum species and maximize the commercial usage of these species.